2014
DOI: 10.1007/s10882-014-9394-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Simultaneous Prompting on the Acquisition of Calculating Elapsed Time in Children with Autism

Abstract: Simultaneous prompting has been effective in teaching a variety of skills, of different levels of complexity, to children with learning difficulties. The current study replicated and extended previous research by teaching three children with Autism to calculate elapsed time. Elapsed time is the duration from a start to end time. When the minutes of the start time are greater than the end time, regrouping is necessary. Simultaneous prompting was used to teach participants to discriminate the type of problem and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…To assess chained tasks, investigators used a single-opportunity method with 26 participants (e.g., assessed performance on a task analysis until error was made; e.g., Hudson et al, 2013) in seven studies and a multiple-opportunity method with 16 participants (e.g., discontinued assessment when an error was made; e.g., Fetko et al, 2013) in five studies. Assessment in one study consisted of permanent product recording with three participants (i.e., Ramirez et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To assess chained tasks, investigators used a single-opportunity method with 26 participants (e.g., assessed performance on a task analysis until error was made; e.g., Hudson et al, 2013) in seven studies and a multiple-opportunity method with 16 participants (e.g., discontinued assessment when an error was made; e.g., Fetko et al, 2013) in five studies. Assessment in one study consisted of permanent product recording with three participants (i.e., Ramirez et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Investigators have predominantly examined the effects of the SP procedure with individuals with intellectual disability ( n = 45; e.g., Batu, 2008). They also have conducted research with individuals with ASD ( n = 22; e.g., Ramirez, Cengher, & Fienup, 2014); developmental disabilities ( n = 8; e.g., Ozen, Ergenekon, & Ulke-Kurkcuoglu, 2017); multiple disabilities, such as intellectual disability, cerebral palsy, and developmental disabilities or physical disabilities and developmental disabilities ( n = 10; e.g., MacFarland-Smith, Schuster, & Stevens, 1993); attention deficit hyperactivity disorder ( n = 3; Hudson et al, 2013); typical development ( n = 2; e.g., Parker & Schuster, 2002); and emotional and behavioral disorders ( n = 1; i.e., Hudson et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Turkey, it is seen that goals of the multiplication skills are increasingly difficult from the second-grade level to the fourth one in the primary school mathematics program (Ministry of National Education, 2018) and multiplication is taught as a short way of addition. The skill of In the studies researching the effect of the SP in teaching mathematical skills to special needs students with poor mathematical performance, it is observed that the skills of recognizing numbers (Akmanoğlu and Batu, 2004), telling time (Karabulut and Yıkmış, 2010), recognizing numbers and telling time (Birkan, 2005), basic facts (Arı, Deniz, and Düzkantar, 2010;Fickel, Schuster, and Collins, 1998;McCormick, 2014), operations with decimal numbers (Rao and Kane, 2009), recognizing money (Tümeğ and Sazak-Pınar, 2016) identify mathematical symbols (Gürsel, Tekin-İftar and Bozkurt, 2006), solving time problems (Ramirez, Cengher, and Fienup, 2014); Pythagorean Theorem (Creech-Galloway, Collins, Knight, and Bausch, 2013) and determining the number of objects rapidly (Jimenez and Saunders, 2019) are taken into account as the target behaviors which are discrete or chaining. In these studies, it has been determined that, the instructions through the SP is effective in acquiring the selected target behaviors.…”
Section: Introductionmentioning
confidence: 99%